2011
DOI: 10.1007/s11433-011-4486-7
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of unmodified gold nanoparticles in colorimetric detection

Abstract: This review begins with an overview of the appealing properties and various applications of gold nanoparticles, and briefly summarizes recent advances in using unmodified gold nanoparticles to detect different kinds of targets including nucleic acids, proteins, metal ions and small organic molecules. The key point to the unmodified gold nanoparticle-based visual detection assay is to control dispersion and aggregation of colloidal nanoparticles by targets of interest, which usually relies on affinities between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 106 publications
(105 reference statements)
2
19
0
Order By: Relevance
“…to the crystallization time 21. He et al 22 analyzed the surface acidities of the SAPO‐34 molecular sieve with IR and NH 3 ‐TPD. The results showed that the Brønsted acidic centers are the main sources of the acidity of the molecular sieve.…”
Section: Introductionmentioning
confidence: 99%
“…to the crystallization time 21. He et al 22 analyzed the surface acidities of the SAPO‐34 molecular sieve with IR and NH 3 ‐TPD. The results showed that the Brønsted acidic centers are the main sources of the acidity of the molecular sieve.…”
Section: Introductionmentioning
confidence: 99%
“…1-6, 10-12, [16][17][18][22][23][24][25][26][27] and test set 1 (No. 7-9, [13][14][15][19][20][21]. Another 27 samples prepared with water from the Xiangjiang River were partitioned into calibration set 2 (No.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies [20,21] have shown that the nitrogen-rich melamine have excellent binding capability to AuNPs. There is a strong interaction between AuNPs and melamine with three exocyclic amino groups and three-nitrogen hybrid ring, which can decrease the stability of citrate-stabilized AuNPs against the aggregation.…”
Section: Sample Preparation and Sers Measurementmentioning
confidence: 95%
“…In addition, NaCl is sometimes used for assisting aggregation reactions to adjust the detection sensitivity and dynamic range to a desired concentration range [6,7]. As well as, unmodi ed MNPs-based colorimetric biosensors use NaCl at relatively high concentration to distinguish folded and unfolded ssDNA, [1,8,9]. Since at high ionic strengths, the time course of the MNPs aggregation is much faster, usually data with large errors is obtained.…”
Section: Introductionmentioning
confidence: 99%